A Period Study of the Close Binary V651 Cassiopeiae - Chun-Hwey Kim; Jae Woo Lee (Journal of Astronomy and Space Sciences, 2000)
All times of minimum light of V651 Cas, which is still less studied so far, were analyzed. From our analysis, it was found that the orbital period of the system may have varied in a periodic manner. After assuming that the period change is produced by the light-time effect due to a third body in the system, attempts to derive the orbital elements of the light-time orbit were made. The resultant values for the period, semi-amplitude, and eccentricity of the light-time orbit were 6.y25, 0.d0013, and 0.77, respectively. The future observations of times of minimum light of V651 Cas are needed to confirm the existence of the third body we suggested in this paper.